2011
DOI: 10.2174/187152011795677571
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Sphingolipids in Response to Chemotherapy: A Scope on Leukemias

Abstract: Sphingolipids are major constituents of the cells with emerging roles in the regulation of cellular processes. Deregulation of sphingolipid metabolism is reflected as various pathophysiological conditions including metabolic disorders and several forms of cancer. Ceramides, ceramide-1-phosphate (C1P), glucosyl ceramide (GluCer), sphingosine and sphingosine-1-phosphate (S1P) are among the bioactive sphingolipid species that have important roles in the regulation of cell death, survival and chemotherapeutic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 211 publications
(211 reference statements)
1
2
0
Order By: Relevance
“…TMZ also causes DNA double-strand breaks and has been shown to promote the accumulation of ceramide in GBM cells [38]. This is consistent with the known effects of many chemotherapies, which often activate ceramide formation through multiple mechanisms, including the activation of ceramide synthases, with this ceramide accumulation playing a major role in the mechanism of action of many of these agents [39][40][41]. Thus, the current therapies for GBM work in part by altering sphingolipid metabolism to enhance pro-apoptotic ceramide levels.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…TMZ also causes DNA double-strand breaks and has been shown to promote the accumulation of ceramide in GBM cells [38]. This is consistent with the known effects of many chemotherapies, which often activate ceramide formation through multiple mechanisms, including the activation of ceramide synthases, with this ceramide accumulation playing a major role in the mechanism of action of many of these agents [39][40][41]. Thus, the current therapies for GBM work in part by altering sphingolipid metabolism to enhance pro-apoptotic ceramide levels.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the current therapies for GBM work in part by altering sphingolipid metabolism to enhance pro-apoptotic ceramide levels. Heightened ceramide metabolism via, for example, the enhanced levels of sphingosine kinases, acid ceramidase or glucosylceramide synthase, commonly observed in many cancers, may clear this elevated ceramide and overcome radio/chemotherapy [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…TMZ also causes DNA double-strand breaks and has been shown to promote the accumulation of ceramide in GBM cells [125]. This is consistent with the known effects of many chemotherapies, which often activate ceramide formation through multiple mechanisms, including the activation of ceramide synthases, with this ceramide accumulation playing a major role in the mechanism of action of many of these agents [90,[129][130][131][132][133][134][135]. Thus, the current therapies for GBM work in part by altering sphingolipid metabolism to enhance pro-apoptotic ceramide levels.…”
Section: Targeting Sphingolipids In Gbmsupporting
confidence: 59%
“…Thus, the current therapies for GBM work in part by altering sphingolipid metabolism to enhance pro-apoptotic ceramide levels. Heightened ceramide metabolism via, for example, the enhanced levels of sphingosine kinases, acid ceramidase or glucosylceramide synthase, commonly observed in many cancers, may clear this elevated ceramide and overcome radio/chemotherapy-induced cell death, providing a mechanism for cancer resistance to these therapies [129][130][131]136]. Notably, analysis of the expression levels of sphingolipid metabolic enzymes in GBM show small but significant differences compared to the normal brain (Figure 3).…”
Section: Targeting Sphingolipids In Gbmmentioning
confidence: 99%
“…Appreciation of the large number of variations in ceramide structure and subcellular localization has led to the recogniztion that ceramide signaling effects might be cataloged according to their molecular structures. Thus far, emphasis has been placed on fatty acid chain length and glycosylation or phosphorylation of the sphingolipid [109111]. Earlier studies demonstrated that complex sphingolipids including gangliosides [112], and long-chain naturally occurring ceramides, i.e., up to 24 carbon atoms in length [113] function by stimulating positive cellular responses such as growth, while sphingosine-containing lipids, including shorter-chain ceramides, have inhibitory effects that result in increased apoptosis, cytotoxicity, or impaired growth [112, 114, 115].…”
Section: Ceramides- Reviewedmentioning
confidence: 99%